A city called heaven : Chicago and the birth of gospel music - Marovich, Robert M. (Urbana : University of Illinois Press, 2015)
In A City Called Heaven, gospel announcer and music historian Robert Marovich shines a light on the humble origins of a majestic genre and its indispensable bond to the city where it found its voice: Chicago. Marovich follows gospel music from early hymns and camp meetings through the Great Migration that brought it to Chicago. In time, the music grew into the sanctified soundtrack of the city's mainline black Protestant churches. In addition to drawing on print media and ephemera, Marovich mines hours of interviews with nearly fifty artists, ministers, and historians--as well as discussions with relatives and friends of past gospel pioneers--to recover many forgotten singers, musicians, songwriters, and industry leaders. He also examines how a lack of economic opportunity bred an entrepreneurial spirit that fueled gospel music's rise to popularity and opened a gate to social mobility for a number of its practitioners. As Marovich shows, gospel music expressed a yearning for freedom from earthly pains, racial prejudice, and life's hardships. In the end, it proved to be a sound too mighty and too joyous for even church walls to hold.
Acknowledgments -- Introduction -- Roots -- Got on my traveling shoes : black sacred music and the great migration -- "When the fire fell" : the sanctified church contribution to Chicago gospel music -- Sacred music in transition : Charles Henry Pace and the Pace Jubilee Singers -- Turn your radio on : Chicago sacred radio broadcast pioneers -- "Someday, somewhere" : the formation of the gospel nexus -- Sweeping through the city : Thomas A. Dorsey and the gospel nexus (1932-1933) -- Across this land and country : new songs for a new era (1933-1939) -- From Birmingham to Chicago : the great migration of the gospel quartet -- Branches -- Sing a gospel song : the 1940s, part one -- "If it's in music -- we have it" : the fertile crescent of gospel music publishing -- "Move on up a little higher" : the 1940s, part two -- Postwar gospel quartets : "rock stars of religious music" -- The gospel caravan : midcentury melodies -- "He could just put a song on his fingers" : second-generation gospel choirs -- "God's got a television" : gospel music comes to the living room -- "tell it like it is" : songs of social significance -- One of these mornings : Chicago gospel at the crossroads -- Appendix A. 1920s African American sacred music recordings made in Chicago -- Appendix B. African American sacred music recordings made in Chicago, 1930-1941.
Vendor-supplied metadata.
Includes bibliographical references (pages 389-399) and indexes.
Keywords: Gospel music -- Illinois -- Chicago -- History; MUSIC / Instruction & Study / Voice; MUSIC / Lyrics; MUSIC / Printed Music / Vocal; MUSIC / Religious / Gospel; Gospel music; Illinois -- Chicago; Chicago (Ill.) -- History -- 20th century; Electronic books; Electronic books; Electronic books; History